2019
DOI: 10.1016/j.jmps.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary effect on nanoindentation: A multiscale discrete dislocation dynamics model

Abstract: Nanoindentation is a convenient method to investigate the mechanical properties of materials on small scales by utilizing low loads and small indentation depths.However, the effect of grain boundaries (GB) on the nanoindentation response remains unclear and needs to be studied by investigating in detail the interactions between dislocations and GBs during nanoindentation. In the present work, we employ a threedimensional multiscale modeling framework, which couples three-dimensional discrete dislocation dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…But not only the pure number of blocks below the indenter is relevant, also the presence of geometrically necessary dislocation accumulation close to grain boundaries must be considered. This has been shown experimentally by Yang and Vehoff (2007) and, very recently, by discrete dislocation dynamic simulations of Lu et al (2019). Figure 12 shows a view through the indented model in our simulations.…”
Section: Discussionsupporting
confidence: 81%
“…But not only the pure number of blocks below the indenter is relevant, also the presence of geometrically necessary dislocation accumulation close to grain boundaries must be considered. This has been shown experimentally by Yang and Vehoff (2007) and, very recently, by discrete dislocation dynamic simulations of Lu et al (2019). Figure 12 shows a view through the indented model in our simulations.…”
Section: Discussionsupporting
confidence: 81%
“…It was concluded that the difficulty in the slip transfer across GBs is pronounced at the GBs corresponding to poorly aligned slip systems and consequently, associated with the low values of m ′ . Focusing on the smaller scales than the continuum level, a discrete dislocation study by Lu et al [117] has recently investigated a bicrystal indented at the area of a GB. Figure 8 in [117] is reproduced here in Fig.…”
Section: Theoretical and Numerical Concepts For Slip Transfermentioning
confidence: 99%
“…Focusing on the smaller scales than the continuum level, a discrete dislocation study by Lu et al [117] has recently investigated a bicrystal indented at the area of a GB. Figure 8 in [117] is reproduced here in Fig. 6 and shows two plateaus in the force data which are associated with displacement bursts at the order of 10% of burgers vector magnitude ( b = 0.25nm ) given in Table 1 in [117].…”
Section: Theoretical and Numerical Concepts For Slip Transfermentioning
confidence: 99%
“…Therefore, the deformation is easier for the BCC crystal structure. It is reported that the nanoindentation hardness inside the grains was lower than that near the grain boundaries due to the grain boundaries strengthening effect [18]. Due to the different scales of the β phase grain sizes and nanoindentaion, it is unclear whether the deformation area is inside the β phase grains or in the β phase grain boundaries.…”
Section: Mechanical Properties Of the Shear Bandmentioning
confidence: 99%